Requirement of Gamma-Carboxyglutamic Acid Modification and Phosphatidylserine Binding for the Activation of Tyro3, Axl, and Mertk Receptors by Growth Arrest-Specific 6 - Geng, Ke; Kumar, Sushil; Kimani, Stanley G.; Kholodovych, Vladyslav; Kasikara, Canan; Mizuno, Kensaku; Sandiford, Oleta; Rameshwar, Pranela; Kotenko, Sergei V.; Birge, Raymond B. (Frontiers in Immunology, 2017)
The TAM receptors (Tyro3, Axl, and Mertk) are homologous type I receptor tyrosine kinases that have critical functions in the clearance of apoptotic cells in multicellular organisms. TAMs are activated by their endogenous ligands, Growth arrest specific-6 (Gas6), and Protein S (Pros1), that function as bridging molecules between externalized phosphatidylserine (PS) on apoptotic cells and the TAM ectodomains. However, the molecular mechanisms by which Gas6/Pros1 promote TAM activation remains elusive. Using TAM/IFNR1 reporter cell lines to monitor functional TAM activity, we found that Gas6 activity was exquisitely dependent on Vitamin K-mediated -carboxylation, whereby replacing Vitamin K with anti-coagulant Warfarin, or by substituting glutamic acid residues involved in PS binding, completely abrogated Gas6 activity as a TAM ligand. Furthermore, using domain and point mutagenesis, Gas6 activity also required both an intact Gla domain and intact EGF-like domains, suggesting these domains function cooperatively in order to achieve TAM activation. Despite the requirement of -carboxylation and the functional Gla domain, non--carboxylated Gas6 and Gla deletion/EGF-like domain deletion mutants still retained their ability to bind TAMs and acted as blocking decoy ligands. Finally, we found that distinct sources of PS-positive cells/vesicles (including apoptotic cells, calcium-induced stressed cells, and exosomes) bound Gas6 and acted as cell-derived or exosome-derived ligands to activate TAMs. Taken together, our findings indicate that PS is indispensable for TAM activation by Gas6, and by inference, provides new perspectives on how PS, regulates TAM receptors and efferocytosis.